Violent Attitudes and Antisocial Behavior: Examining the Code of the Street's Generalizability among a College Sample. Issue 9 (2nd September 2017) - Intravia, Jonathan; Wolff, Kevin T.; Gibbs, Benjamin R.; Piquero, Alex R.
ABSTRACT: Drawing on Elijah Anderson's (1999) Code of the Street thesis, this study assesses the generalizability of street code attitudes. Using a sample of college students from a large Midwest university, the current study contributes to the literature by examining: (1) the generalizability of street code attitudes; (2) the correlates of street code attitudes, including various forms of strain; and (3) the predictive power of street code attitudes on criminal and non-criminal behavior. Our results reveal that street code attitudes are generalizable to college students, strain constructs are important correlates of street code attitudes, and street code attitudes are associated with criminal behavior. However, the effect of street code attitudes on criminal behavior becomes non-significant once measures of strain are included. Further, street code attitudes do not predict non-criminal behavior.